El queísmo en la historia - Blas Arroyo, José Luis; Velando Casanova, Mónica (De Gruyter, 2022)
The book offers a panchronic analysis of queísmo, one of the oldest variational phenomena in Spanish syntax, from the Classical era to this day. Within the framework of historical sociolinguistics and on the empirical basis of a broad corpus of texts close to the pole of immediacy, the study analyzes the factors that have determined this variation at various points in time.